Foal Monocyte-Derived Dendritic Cells Become Activated upon Rhodococcus equi Infection - Flaminio, M. Julia B. F. (American Society for Microbiology (ASM), 2009)
Susceptibility of foals to Rhodococcus equi pneumonia is exclusive to the first few months of life. The objective of this study was to investigate the immediate immunologic response of foal and adult horse antigen-presenting cells (APCs) upon infection with R. equi. We measured the activation of the antigen-presenting major histocompatibility complex (MHC) class II molecule, costimulatory molecules CD40 and CD86, the cytokine interleukin-12 (IL-12), and the transcriptional factor interferon regulatory factor 1 (IRF-1) in monocyte-derived macrophages (mMOs) and dendritic cells (mDCs) of adult horses and foals of different ages (from birth to 3 months of age) infected with virulent R. equi or its avirulent, plasmid-cured derivative. Infection with virulent or avirulent R. equi induced (P ≤ 0.01) the expression of IL-12p35 and IL-12p40 mRNAs in foal mMOs and mDCs at different ages. This response was likely mediated by the higher (P = 0.008) expression of IRF-1 in foal mDCs at birth than in adult horse mDCs. R. equi infection promoted comparable expression of costimulatory molecules CD86 and CD40 in foal and adult horse cells. The cytokine and costimulatory response by foal mDCs was not accompanied by robust MHC class II molecule expression. These data suggest that foal APCs detect the presence of R. equi and respond with the expression of the Th1-inducing cytokine IL-12. Nevertheless, there seems to be a limitation to MHC class II molecule expression which we hypothesize may compromise the efficient priming of naïve effector cells in early life.